Tax Regulation Challenges in the Digital Economy Era: Legal Analysis and Implications in Indonesia - Rizqiyanto, Naufal; Rizqi, M.; Afsa, Fahmil Alfian Rizkia; Berrahlia, Badreddine (Faculty of Law Universitas Trunojoyo Madura, 2025)
The rapid growth of the digital economy has transformed global business landscapes, creating significant challenges for tax regulation in Indonesia. This study aims to identify the obstacles in regulating the digital economy, analyze the impact of legal uncertainty on taxpayer compliance, and evaluate how technological infrastructure limitations hinder effective tax enforcement. Applying normative legal methods and an exploratory approach, this research employs statute and case-based approaches, with data collected from primary legislation and secondary literature sources. The findings indicate that legal uncertainties regarding MSME identification in digital transactions, digital economy subjects, permanent establishment (PE) status, and tax collection mechanisms significantly reduce taxpayer compliance. Additionally, the limited technological infrastructure is the major obstacle to enforcing tax regulations effectively. This research contributes to emphasize the need of the clear legal frameworks and robust technological systems to address those challenges. In conclusion, to resolve the issues requires regulatory reforms to provide unambiguous guidelines for digital transactions, increased investments in technological infrastructure, and the development of comprehensive frameworks to enhance compliance and enforcement. The study recommends a strategic focus on harmonizing legal standards and technological advancements to support a sustainable tax ecosystem in the digital economy.